PENGINTEGRALAN MENGGUNAKAN ATURAN SIMPSON UNTUK INTERVAL TITIK YANG TIDAK SAMA - Fitriani Fitriani; Akhmad Yusuf; Yuni Yulida (EPSILON: JURNAL MATEMATIKA MURNI DAN TERAPAN, 2019)
In general, numerical integration is carried out at the same point intervals. But in reality, it is sometimes faced with the problem of integrating a function with unequal point intervals. One method to calculating integrals at unequal interval points is the Simpson rule. Based on it, the research aims to form a general formula of numerical integration for unequal interval points and Simpson rule equation by using the Newton interpolation formula with divided differences, also an errors for unequal interval points by integrating the Taylor’s series. The results of this research were obtained a general formula of numerical integration for unequal interval points, general formula of Simpson's 1/3-rule, general formula of the Simpson's 3/8-rule, and an error for each other’s Simpson’s rules.Keywords : Numerical Integration, Simpson's 1/3-Rule, Simpson's 3/8-Rule, Error.